Luid ka, Clark: a morphological landscape mapping method for documenting memoryscapes in the landscape context of identified historical places in Clark Freeport Zone - Diaz, Cathleen Carpio; Cathe Desiree S. Nadal (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
This thesis examines the transformation of Clark Freeport Zone (CFZ) from a former
U.S. military base to a major economic zone, with a focus on documenting its cultural
memory amidst rapid urban modernization. While CFZ's Design Standards and
Guidelines (DSG) emphasize economic growth and urban competitiveness, they
provide limited provisions for heritage and memory conservation, raising concerns
about the weakening of CFZ's historical identity.

Employing the Morphological Landscape Mapping Method (MLMM), the study
integrates archival research, qualitative interviews, focus group discussions,
participatory memory mapping, and spatial analysis to document community actors'
collective memories linked to CFZ's Identified Historical Places (IHPs). The findings
reveal three distinct typologies of memoryscapes-key, fragmented, and
underrecognized-highlighting both continuity and loss across generational cohorts
(Gen X, Gen Y, and Gen Z).

These findings underscore the need to consider cultural memory conservation within
the context of urban growth. This presents an opportunity to explore the integration of
memoryscapes into planning efforts, with a primary focus on documenting the
collective memory of community actors to emphasize CFZ's cultural identity. The thesis
proposes a CFZ Memoryscape - Planning Integration Guide, offering recommendations for future planning initiatives aimed at incorporating memoryscapes
into developments, thereby preserving the cultural identity of CFZ amidst
modernization.
Include appendices
Thesis (Master of Tropical Landscape Architecture) -- University of the Philippines Diliman
Keywords: Collective memory -- Clark Freeport Zone; Group identity -- Clark Freeport Zone